ANALISIS PENGARUH UPAH, PENDIDIKAN, PENDAPATAN SUAMI DAN JUMLAH TANGGUNGAN KELUARGA TERHADAP CURAHAN JAM KERJA PEREMPUAN MENIKAH DI IKM MEBEL KABUPATEN JEPARA - Ayu Susanti Sidauruk; Nenik Woyanti (Diponegoro Journal of Economics, 2014)
ABSTRACTIncreasing number of married women who enter the labor market, indicating that the greater the role of married women in the household economy and also in development. This study aims to analyze the factors that affect the flow of working hours of married women in IKM Furniture Jepara regency. The factors may include wages (X1), education (X2), husband's income (X3) and the number of dependents (X4).The research was conducted in two selected districts, namely District and District Annual Mlonggo, with a sample of 100 respondents from a total population of 1,596 labors. Sampling with proportional random sampling method. Method of data analysis used in this study is a model of multiple linear regression or OLS with outpouring of hours worked as the dependent variable and the four independent variables, namely wages (X1), education (X2), husband's income (X3) and the number of dependents (X4). Techniques of data collection using questionnaire-assisted interview (interview).Results of the analysis showed wage variable (X1) and the number of dependents (X4) positive and significant effect of the outpouring of working hours of married women in IKM Furniture Jepara (Y). Education variable (X2) is not affected significantly affect the flow of working hours of married women in IKM Furniture Jepara (Y). Husband's income variable (X3) and a significant negative effect on married women's hours of work flow in IKM Furniture Jepara (Y).